Cneazul Ioan Cantacuzino – un modern al timpurilor vechi? - Adriana Iancu (Revista de Istorie și Teorie Literară)
Through his texts, Ioan Cantacuzino brings to light his taste and his forward-looking views through the contact with the European literature of the time, and also his contribution regarding its development and, especially, the development of the literary language at the end of the 18th century. From a thematic point of view, through his adaptations, the autor anticipates the later modern literature!